PENERAPAN PLAY ACTIVITIES DALAM MENINGKATKAN PERILAKU KERJASAMA ANAK-ANAK PANTI ASUHAN AMIN - Dewi, Aprila; Giovanni Margaret; Mariana Soka; Meiske Yunithree Suparman (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
This program aims to enhance the cooperative behavior of children at the Amin Orphanage through the implementation of play activities. Cooperation skills are essential social behaviors that need to be developed, especially in children. Cooperation through communication, problem-solving, creativity, and self-confidence can shape their social skills. Play activities, involving action, creativity, and sensitivity, support cognitive, motor, emotional development, and enhance social skills and empathy among children. Additionally, play activities make children enjoy their time together. Thus, these elements significantly contribute to active and meaningful learning, building children's self-confidence and social awareness. The results of this program show a significant difference in cooperative behavior before and after the program's implementation.